Ghana : Coastal Wetlands Management - Mohan, P. C. (World Bank, Washington, DC, 2012)
The objectives of the Coastal Wetlands Management Project for Ghana (1993-99) were to maintain the ecological integrity of five key coastal wetland areas by involving the people who derive their livelihood from these ecosystems in the planning and implementation of management programs; to identify and monitor the common resources that benefit the human and bird populations in the wetlands, and manage them without unduly restricting the options of people to derive benefit from the resources. It would also develop capabilities at government and community level for implementing the program. This project was implemented with the assistance of a Global Environmental Trust Fund grant.